Neural responses in autism during movie watching: Inter-individual response variability co-varies with symptomatology - Bolton, Thomas A.W.; Freitas, Lorena G.A.; Jochaut, Delphine; Giraud, Anne-Lise; Van De Ville, Dimitri (NeuroImage (Orlando, Fla.), 2020)
Naturalistic movie paradigms are exquisitely dynamic by nature, yet dedicated analytical methods typically remain static. Here, we deployed a dynamic inter-subject functional correlation (ISFC) analysis to study movie-driven functional brain changes in a population of male young adults diagnosed with autism spectrum disorder (ASD). We took inspiration from the resting-state research field in generating a set of whole-brain ISFC states expressed by the analysed ASD and typically developing (TD) subjects along time. Change points of state expression often involved transitions between different scenes of the movie, resulting in the reorganisation of whole-brain ISFC patterns to recruit different functional networks. Both subject populations showed idiosyncratic state expression at dedicated time points, but only TD subjects were also characterised by episodes of homogeneous recruitment. The temporal fluctuations in both quantities, as well as in cross-population dissimilarity, were tied to contextual movie cues. The prominent idiosyncrasy seen in ASD subjects was linked to individual symptomatology by partial least squares analysis, as different temporal sequences of ISFC states were expressed by subjects suffering from social and verbal communication impairments, as opposed to nonverbal communication deficits and stereotypic behaviours. Furthermore, the temporal expression of several of these states was correlated with the movie context, the presence of faces on screen, or overall luminosity. Overall, our results support the use of dynamic analytical frameworks to fully exploit the information obtained by naturalistic stimulation paradigms. They also show that autism should be understood as a multi-faceted disorder, in which the functional brain alterations seen in a given subject will vary as a function of the extent and balance of expressed symptoms. [Display omitted] •Naturalistic stimulation paradigms are intrinsically well-suited to dynamic analysis.•We derived whole-brain inter-subject functional correlation (ISFC) states.•Homogeneity in state expression fluctuated along incoming movie cues.•Subjects with autism showed more idiosyncratic ISFC state expression.•This heterogeneity is due to individual extent and balance in symptoms.